2021
DOI: 10.7759/cureus.14220
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Extramedullary Plasmacytoma With Rare Osteolytic Lesions

Abstract: Plasmacytomas are malignant tumors characterized by abnormal monoclonal proliferation of plasma cells. They originate either from bone or soft tissue and could be primary or a part of a systemic process during the course of multiple myeloma. Extramedullary plasmacytomas (EPs) in the sinonasal tract or nasopharynx are rare and mostly presented as case reports. We describe a unique case of multiple myeloma involving the nasal cavity and the paranasal sinuses with osteolytic expansile lesions of the first cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
2
Order By: Relevance
“…Alexiou et al reviewed the head and neck EMP in detail and found that the combination of radiation and surgery resulted in a significant lead in 5-year survival, with a 5-year survival rate of approximately 50%. [ 23 ] Moreover, another study revealed that 40% of EMPs spread beyond the primary site and/or developed lymphatic drainage, 62% of patients had deposits in soft tissues and internal organs, and 81% of patients developed bone lesions. [ 12 ] The results of our study on our patient and previous literature review show that nasal EMP has less progression to MM, recurrence and metastasis, which may be related to the short follow-up time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alexiou et al reviewed the head and neck EMP in detail and found that the combination of radiation and surgery resulted in a significant lead in 5-year survival, with a 5-year survival rate of approximately 50%. [ 23 ] Moreover, another study revealed that 40% of EMPs spread beyond the primary site and/or developed lymphatic drainage, 62% of patients had deposits in soft tissues and internal organs, and 81% of patients developed bone lesions. [ 12 ] The results of our study on our patient and previous literature review show that nasal EMP has less progression to MM, recurrence and metastasis, which may be related to the short follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…Through systematic and gradual screening of literature, 20 full texts including 23 patients were finally obtained. [2,5,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Including our patient, a total of 24 patients consisting of 16 men and 8 women, were included in this study. The median age of onset in men was about 52.9 years, and the age ranged from 45 to 63 years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1, врезка). В прилежащей слизистой оболочке В отличие от предыдущих наблюдений G. Pantazidou [9] описал пациента 51 года с клинической картиной, сходной с таковой в нашем случае, и диагнозом «экстрамедуллярная солитарная плазмоцитома носовой полости и носовых синусов с поражением костной ткани». При ИГХ исследовании у этого пациента в опухоли выявлены позитивные маркеры CD79a, CD138.…”
Section: морфологическое исследованиеunclassified
“…Счи тается, что от 11 до 30 % случаев ЭП может прогрес сировать до плазмоклеточной миеломы в течение 10 лет [11]. Так, описан первый случай ЭП, поража ющей области носа и околоносовых пазух, с присутст вием остеолитического поражения шейных позвонков, ключицы и черепа на момент постановки диагноза [12]. Соответственно, при подозрении, выявлении и подтвер ждении ЭП необходимы четкая визуализация опухоли и детальные лабораторные исследования для подтвер ждения или исключения диагноза плазмоклеточной миеломы.…”
Section: диагностика и лечение множественной миеломыunclassified